HRT in Patients over 70 years old – own experiences - Rubersz-Adamska, Grażyna; Surkont, Grzegorz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2002)
There is a lot of controversy on HRT in late postmenopausal women among polish gynecologists. In the study there were assessed the indications, contraindications, types and tolerance of HRT in women over 70 years old – the patients of Menopause Clinic in Institute of Obstetrics and Gynecology Medical University of Łódź in 1999. The most common indication to HRT was osteoporosis. „Tailored HRT” leaded to good tolerance of the therapy.